Liveworksheet Interactive E-Module Effect on Equal Fractions Comprehension at 4th Grade Elementary School - Firdaus, Fery Muhamad; Fadhilah, Nur; Wuryandari, Indriana Trisoma; Fadhli, Rahmat (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2024)
This study seeks to investigate the impact of utilizing the liveworksheet interactive e-module on the comprehension of equal fractions among fourth-grade pupils. This study employed a quantitative methodology, utilizing a quasi-experimental design. The research design employed is a posttest control only-control group design. The sample size for this study consisted of 26 children who were in the 4th grade at SDN 2 Kejambon. The investigation employed a simple random sampling technique. The instrument comprised six descriptive questions. The data analysis was conducted using a T-test as a prerequisite test, including normality and homogeneity tests, with the assistance of SPSS software. The results obtained from the T-test analysis include a t-value of 2.311 and a significance value (2-tailed) of 0.030, which is less than 0.05. The results obtained from the T-test investigation include a t-value of 2.311 and a significance value (2-tailed) of 0.030, which is less than 0.05. The liveworksheet interactive e-module was found to have an impact on the comprehension of the Equal fraction idea. Subsequently, invalid hypothesis (H0) that is